Control interno al departamento de crédito y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito sumak kawsay, cantón Latacunga, año 2023 - Soria Oto, Katerin Dennys (2025)
This paper focuses on the field of Accounting and Auditing, specifically on the impact of internal control on the profitability of a financial institution. The object of study is the Sumak Kawsay Savings and Credit Cooperative in the canton of Latacunga for the period 2023. The research is conducted with the aim of evaluating how the implementation of internal control in the credit department affects its profitability, taking into account the current weaknesses in the credit process that have increased delinquency and affected the financial stability of the cooperative. The research used a mixed methodological approach, applying COSO I to evaluate the risks and effectiveness of internal control, in addition to interviews,